2013
DOI: 10.1071/py12041
|View full text |Cite
|
Sign up to set email alerts
|

Competency requirements for middle and senior managers in community health services

Abstract: The Australian health system has been subjected to rapid changes in the last 20 years to meet increasingly unmet health needs. Improvement of the efficiency and comprehensiveness of community-based services is one of the solutions to reducing the increasing demand for hospital care. Competent managers are one of the key contributors to effective and efficient health service delivery. However, the understanding of what makes a competent manager, especially in the community health services (CHS), is limited. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 16 publications
2
53
0
Order By: Relevance
“…In other high-income countries, nursing management competencies include communication as critical for health systems strengthening (2, 6, 1923). Notwithstanding study setting differences, our results are similar to a UK study among nursing managers which indicated additional training in communication as a need (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other high-income countries, nursing management competencies include communication as critical for health systems strengthening (2, 6, 1923). Notwithstanding study setting differences, our results are similar to a UK study among nursing managers which indicated additional training in communication as a need (43).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that nursing management competencies should include communication, team building, planning, priority setting and problem-solving, performance, health programme, and resource management (2, 6, 1921), especially financial management (22, 23). Change management and community collaboration are other essential competencies required at the district level (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, through a rigorous research process combining a literature review, focus group discussions, an online survey of HSMs and input from a group of expert advisors, a Management Competency Assessment Project (MCAP) conducted in Victoria, Australia, identified six core competencies for middle and senior level managers working in hospitals and community health services (CHS) (Liang et al. 2013a, b). Each of the competencies was further developed, resulting in 79 behavioural items to assess the capabilities of the managers in demonstrating these competencies in their roles (see Table ).…”
Section: The Six Competencesmentioning
confidence: 99%
“…2,3 However, the effects of such programmes on competence and individual or organisational performance have not been assessed and synthesised systematically. Thus, questions arise as to whether or not the various interventions aimed at addressing the gaps in health management and leadership competence actually lead to improvement in individual and organisational performance.…”
Section: Introductionmentioning
confidence: 99%